Upaya Guru Mengimplementasikan Pembelajaran Menggunakan Kurikulum Merdeka di Kelas IV SDS Tarbiyatul Islam Sambas Tahun Pelajaran 2023-2024 - Muslimin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to describe the planning, implementation, and evaluation of the Independent Curriculum (Kurikulum Merdeka Belajar) at SDS Tarbiyatul Islam Sambas in the 2023–2024 academic year. This research employed a qualitative approach with a phenomenological design, using interviews, observations, and documentation as data collection techniques. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that lesson planning was carried out by teachers through the preparation of teaching modules based on learning outcomes, formulation of learning objectives, sequencing of objectives, and assessment planning. The learning process was implemented in three stages: introduction, core activities, and closing, with formative assessments conducted periodically. Evaluation was carried out through formative assessments during the learning process and summative assessments at the end of learning, in accordance with the prepared teaching modules. Despite challenges such as limited facilities and infrastructure, teachers strived to optimize learning in line with the principles of the Independent Curriculum to support the school’s vision and mission.